Long-term outcome of psychodynamic therapy and cognitive-behavioral therapy in social anxiety disorder - Leichsenring, Falk; Salzer, Simone; Beutel, Manfred E.; Herpertz, Stephan; Hiller, Wolfgang; Hoyer, Juergen; Hüsing, Johannes; Joraschky, Peter; Nolting, Bjoern; Poehlmann, Karin; Ritter, Viktoria; Stangier, Ulrich; et al. (The American journal of psychiatry, 2014)
ObjectiveRelatively few studies have examined the long-term outcome of psychotherapy in social anxiety disorder. The authors previously reported findings of a clinical trial comparing cognitive-behavioral therapy (CBT), psychodynamic therapy, and a wait-list control. The purpose of the present study was to follow the participants’ status over the ensuing 24 months.MethodOutpatients with social anxiety disorder who were treated with CBT (N=209) or psychodynamic therapy (N=207) in the previous trial were assessed 6, 12, and 24 months after the end of therapy. Primary outcome measures were rates of remission and response.ResultsFor both CBT and psychodynamic therapy, response rates were approximately 70% by the 2-year follow-up. Remission rates were nearly 40% for both treatment conditions. Rates of response and remission were stable or tended to increase for both treatments over the 24-month follow-up period, and no significant differences were found between the treatment conditions after 6 months.ConclusionsCBT and psychodynamic therapy were efficacious in treating social anxiety disorder, in both the short- and long-term, when patients showed continuous improvement. Although in the short-term, intention-to-treat analyses yielded some statistically significant but small differences in favor of CBT in several outcome measures, no differences in outcome were found in the long-term.